2011
DOI: 10.3109/10826084.2011.579677
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Misuse Among 17- to 18-Year-Old Croatian Adolescents: Correlation with Scholastic Variables and Sport Factors

Abstract: Substance use and misuse (SUM) and the relation to physical activity/exercise/athletic participation (sport factors) and scholastic achievement are rarely studied in Croatia. The aim of this study was: (1) to investigate the SUM habits in Croatian adolescents (17-18 years of age, 254 males, and 218 females), and (2) to study potential gender-specific interrelationships between scholastic and sport factors in relation to SUM. The testing was done using an extensive, anonymous, self-administered questionnaire th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 21 publications
13
47
3
Order By: Relevance
“…To the best of our knowledge, only 1 study has investigated the problem of substance misuse, and the authors have reported that 36% of adolescents in the city of Gjilan were smokers, with no significant difference between girls and boys [2]. These findings are consistent with previous studies on the prevalence of smoking among adolescents in the region (a former Yugoslav territory) [3,4].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…To the best of our knowledge, only 1 study has investigated the problem of substance misuse, and the authors have reported that 36% of adolescents in the city of Gjilan were smokers, with no significant difference between girls and boys [2]. These findings are consistent with previous studies on the prevalence of smoking among adolescents in the region (a former Yugoslav territory) [3,4].…”
Section: Introductionsupporting
confidence: 82%
“…Surveys were performed using a self-administered questionnaire, which was previously used and found to Smoking in adolescence: Prevalence and correlates Nr 2 155 be valid in a similar sample of subjects in surrounding countries [3,4]. Although the questionnaire consisted of a broad variety of questions, the study focused on sociodemographic variables, sport-related factors, familial monitoring (predictors), and cigarette consumption data (dependent variable).…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…alcohol is consumed regularly with the meal, but intoxication is not socially accepted). However, there is strong epidemiological evidence that excessive consumption of alcohol is a growing problem in Croatia [28]. Taking into account the specific military environment (which in general accepts alcohol consumption), we may highlight that alcohol consumption in the Croatian Army should be precisely monitored, although our data showed relatively low levels of alcohol consumption in the studied sample of SAF members.…”
Section: Discussioncontrasting
confidence: 43%
“…In short, studies reported younger age, low military rank and subjectively poor mental health score as the risk factors for heavy alcohol drinking [21,22]. Additionally, those soldiers who have never been married, and/or have been separated to "I binge a few times a week") and by the Alcohol Use Disorders Identification Test (AUDIT) scale [16,28]. The subjects were additionally grouped according to AUDIT results into those who practice harmful drinking (scores of 11 or above) vs. non-harmful drinking (scores below 11).…”
Section: Introductionmentioning
confidence: 99%